The Message Of Da'wah In Films And Criticism Of The Concept Of Reincarnation - Fauziyah; Fatima, Nuzhat (Communicator: Journal of Communication, 2024)
The concept of reincarnation is often a controversial topic because it raises deep theological debates. Film, as a mass communication medium, has the potential to spread thoughts or beliefs, including reincarnation. One of the films that raises this theme is Along With Gods 2: The Last 49 Days, a production work from South Korea. Seeing the potential negative impact of the concept of reincarnation on Muslims, this study aims to analyse and criticise the concept based on the teachings of Islamic law—qualitative method with Charles Sander Peirce's semiological approach. The data obtained from the film were analysed using Peirce's semiotic theory through the analysis of the concept of trichotomy. The results of the study showed that there were 25 scenes related to reincarnation in the film, of which eight messages of faith and three moral messages were found that contained da'wah values. Criticism of the concept of reincarnation is based on its irrationality and contradiction with Islamic teachings. In Islam, resurrection is believed to occur on Yaumul Ba'ats, the day of resurrection to account for charity, and not in the form of rebirth in the world as depicted in the concept of reincarnation.